Sort by

- Relevance
- |Time

Note that Σ(

**k**= 5 to ∞) C(**k**-1,**k**-5)**k**^3/2^**k**...to ∞) (k-1)(k-2)(k-3)(k-4) * k^3 x^**k**{at x = 1/2} = (1/24) x^5 * Σ(**k**...%29+C%28k-1%2C+**k**-5%29+**k**^3%2F2^**k**I hope...1 Answers · Science & Mathematics · 29/07/2014

0=<

**k**=<4 points of intersection are (-1,1) and (-3,1...solve it with 2 quadratic equations, one for each point. You will get**k**. For (-1,1),**k**is between (0,2) For (-3,1),**k**is...2 Answers · Science & Mathematics · 02/09/2008

2kx² - 12x + (

**k**+7) = 0 Solve for**k**b² - 4ac = 0 (b = -12, a = 2k and c =**k**...8 ..........-k² - 7k + 18 = 0 .......... k² + 7k - 18 = 0 ........ (**k**- 2) (**k**+ 9) = 0 ......**k**- 2 = 0..........................**k**+ 9 = 0**k**- 2 + 2 = 0 + 2...4 Answers · Science & Mathematics · 12/09/2010

Hello, x³ – (

**k**+ 1)x + 2k = 0 = = = = = = = = = = = = = = = = = = = = = = Obviously, if**k**=0, we obtain... prime and**k**≠0: Then 2k has four divisors: 1, 2,**k**and 2k. Rational root theorem induce that if a rational root exists...2 Answers · Science & Mathematics · 10/12/2012

Goal: To get "

**k**" isolated by itself. a.) 0 = 14 +**k**In order to isolate... so that the 3.3 on the variable side will turn into 0 and will not count. -0.8 =**k**+ 3.3 -0.8 - 3.3 =**k**+ 3.3 - 3.3 -4.1 =**k**+ 0 Since the zero does...3 Answers · Science & Mathematics · 16/06/2011

### an=sum

**k**=0 to**k**=n from 10 (-**k**^2).The limit of this sequence belongs to the set a)Q b) [-1,0) c) R/Q?a(n) = Σ(

**k**= 0 to ∞) 10^(-**k**^2) is irrational (choice C, assuming you mean...bit more, showing that it is transcendental. Let p(n) = Σ(**k**= 0 to n) 10^(n -**k**^2) and q(n) = 10^n. Then, |Σ(**k**= 0 to ∞) 10...2 Answers · Science & Mathematics · 13/04/2013

(

**k**- 2)x^2 + (**k**- 5)x - 5 = 0 The roots are equal if the discriminant... discriminant, b^2 - 4ac, evaluated as follows: (**k**- 5)^2 - 4(**k**- 2)(-5) And we want this to be equal to zero. (**k**...3 Answers · Science & Mathematics · 06/12/2008

Let

**k**≥ 2. Then p_(**k**- 1) + 3k - 2 = (**k**- 1)[3(**k**- 1) - 1]/2 + (6k - 4)/2 = [(**k**- 1)(3k - 3 - 1) + 6k - 4]/2 = [(**k**- 1)(3k - 4) + 6k - 4]/2 = (3k² - 7k...1 Answers · Science & Mathematics · 13/09/2009

**k*** 3^**k**= 1,000,000,000 Start by taking the natural logarithm of both sides of the equation to remove that variable from the exponent:*** ln(3^**k**)(**k**) = ln(1,000,000,000) Now the exponent of a factor here can be ...1 Answers · Science & Mathematics · 21/09/2008

**k**(**k**- 5) > 0 in two cases: 1)**k**> 0 and (**k**- 5) > 0 2)**k**< 0 and (**k**- 5) < 0 In case 1,**k**> 0 and**k**> 5; both of these are true when**k**> 5. In case 2,**k**...1 Answers · Science & Mathematics · 11/04/2010

##### Ads

related to**K**